Towards Smarter Consumer Protection Rules for Digital Services - Alexandre de Streel; Anne-Lise Sibony (International Telecommunications Society (ITS), 2017)
This CERRE Policy Report makes recommendations, on the basis of the most recent academic literature, to improve EU consumer protection rules for digital services. Digital services are defined broadly and cover the main current legal categories, i.e. the information society services, the provision of digital content, the electronic communications service and the audiovisual media services. The Report deals with the horizontal consumer protection rules which have just be evaluated by the European Commission as well as sector-specific rules whose some are currently reviewed by the EU legislator.
Keywords: 330